Improving Students’ Writing Skill Using Think Pair Share Strategy - Rhema Florensyulia Eveline M; Doni Anggoro Ari Santoso; Nina Dwiastuty (JEdu: Journal of English Education, 2022)
The purpose of this study is to improve students' writing skills in English using Think Pair Share Learning Strategy. The method for this research is Classroom Action Research. The researcher will try to use the Think Pair Share strategy properly to solve problems in Teaching Writing at BIT BINA AULIA Vocational High School. The object of the research in this study is grade 10 students. Think Pair Share not only makes students think individually but also builds Communication Skills when all students are asked to present and share their thoughts and the result of discussions with their partners, or in front of the class. This research is established in two cycles within four steps for each cycles: plan, action, observation, and reflection. In reflections, the researcher finds things to improve the next cycle. Students’ worksheets have to show a good result to see how much students have improved their writing skills in hope and conclusion that the Think Pair Share Learning strategy can be used as a variation of learning to improve English writing skills